2023
DOI: 10.1128/mbio.00416-23
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Immune Evasion and Host Range Expansion by the SARS-CoV-2 B.1.1.529 (Omicron) Variant

Abstract: The recently emerged SARS-CoV-2 Omicron variant with numerous mutations in the spike protein has rapidly become the dominant strain, thereby raising concerns about the effectiveness of vaccines. Here, we found that the Omicron variant exhibits a reduced sensitivity to serum neutralizing activity induced by a three-dose inactivated vaccine but remains sensitive to entry inhibitors or an ACE2-Ig decoy receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The S protein binds to the hACE2 receptor and mediates entry into susceptible host cells. Studies showed that the S protein of Omicron variant utilizes the hACE2 receptor with enhanced efficiency than ancestral SARS-CoV-2 strains, a feature that has been speculated to contribute to rapid transmission of the virus [18,2729]. Omicron BA.1 S protein presents an enhanced RBD-ACE2 binding interface through the interactions of amino acids N501Y, Q498R, and T478K with the host receptor in target cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The S protein binds to the hACE2 receptor and mediates entry into susceptible host cells. Studies showed that the S protein of Omicron variant utilizes the hACE2 receptor with enhanced efficiency than ancestral SARS-CoV-2 strains, a feature that has been speculated to contribute to rapid transmission of the virus [18,2729]. Omicron BA.1 S protein presents an enhanced RBD-ACE2 binding interface through the interactions of amino acids N501Y, Q498R, and T478K with the host receptor in target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron BA.1 variant is more immune evasive and less virulent than the other major identified variants [10,1215,18,23,27,28,30,31,3436]. In Syrian hamsters, the SARS-CoV-2 B.1 D614G produced significant illness, higher viral loads in secretions and tissues, while the Omicron BA.1-inoculated animals were subclinical and had reduced virus replication and shedding [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These antibodies effectively block the interaction between RBD and ACE2, highlighting the RBM, particularly the ACE2 binding interface, as the pivotal neutralizing epitope. Moreover, all variants of SARS-CoV-2 still utilize ACE2 as the receptor for host cell entry ( 14 , 15 ). Therefore, targeting the RBD, particularly the ACE2 binding interface, in antigen design remains an effective approach.…”
Section: Introductionmentioning
confidence: 99%